Preparation method of high-temperature-resistant and salt-resistant polyacrylamide for oil displacement of oil field

By using gradient composite modification materials and a complex multi-step preparation process, the problems of weak interfacial bonding and uneven dispersion in traditional modification methods were solved, and high-temperature resistant and salt-resistant polyacrylamide was prepared, which improved the oil displacement efficiency of deep high-temperature and high-salt reservoirs.

CN121135972APending Publication Date: 2025-12-16GREEN CHEM (DONGYING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511276791.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

This invention addresses the technical problem of the performance of partially hydrolyzed polyacrylamide in high-temperature and high-salinity oil reservoirs. It solves the problem of easy thermal degradation and a sharp drop in viscosity due to charge neutralization in high-temperature and high-salinity oil reservoirs.

Method used

By employing novel modified materials and supporting preparation processes, a ternary gradient structure design of "layered double hydroxide/polydopamine/sulfonated polyaldehyde ketone" was used to achieve synergistic effects of ion shielding, interfacial adhesion, and temperature resistance enhancement. Combined with stepwise dispersion activation, gradient polymerization, and enhanced crosslinking processes, the problems of weak interfacial bonding and uneven dispersion in traditional modification methods were effectively solved. Finally, a novel polyacrylamide with high temperature resistance, strong salt resistance, and excellent long-term stability was prepared.

Benefits of technology

The polymer exhibits high temperature resistance, salt resistance, and long-term stability in deep, high-temperature, and high-salinity oil displacement applications, significantly improving oil displacement efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005586304990000111
    Figure BDA0005586304990000111
  • Figure BDA0005586304990000121
    Figure BDA0005586304990000121
Patent Text Reader

Abstract

The invention discloses a preparation method of high-temperature-resistant and salt-resistant polyacrylamide for oil displacement of an oil field in the technical field of oilfield chemical agents, which comprises the following steps: firstly, preparing a layered double hydroxide precursor by a hydrothermal method, modifying by polydopamine to enhance the surface adhesion, and then synthesizing a polyfunctional group sulfonated polyether ether ketone cross-linking agent containing double bonds and sulfo groups, so as to obtain the high-temperature-resistant and salt-resistant polyacrylamide for oil displacement of the oil field. Performing in-situ free radical polymerization on the three components to obtain a gradient composite modified material; then dispersing and activating the modified material, copolymerizing with acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-vinyl pyrrolidone and other monomers, controlling the temperature gradient to initiate and polymerize, adding a cross-linking agent at the later stage to reinforce a network structure, and washing, granulating, drying and crushing to obtain the product. According to the method, the temperature resistance, salt resistance and shear resistance of polyacrylamide are remarkably improved through synergistic enhancement of gradient structure design and a multi-step complex process, and the method is suitable for oil displacement application of an oil field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oilfield chemical agents, specifically to a method for preparing high-temperature resistant and salt-resistant polyacrylamide for oilfield flooding. Background Technology

[0002] The core of tertiary oil recovery technology lies in enhancing crude oil recovery through the injection of high-molecular-weight polymers. Polyacrylamide (PAM), due to its excellent water solubility, viscosity-enhancing properties, and controllable molecular structure, has long been widely used as a mainstream oil displacement agent in oilfield development. However, as global oil and gas resource development extends to deeper, higher-temperature, and higher-salinity reservoirs, the performance limitations of traditional partially hydrolyzed polyacrylamide are becoming increasingly apparent. Under high-temperature conditions, the amide groups in the molecular chain of this polymer are prone to thermal degradation, leading to a rapid decrease in molecular weight. In high-salinity reservoirs, high-valence metal ions combine with carboxyl groups on the PAM molecular chain, neutralizing their negative charge and disrupting the hydration layer of the molecular chain. This causes a sharp drop in the viscosity of the polymer solution, failing to effectively support the oil displacement channels in the reservoir rock pores, ultimately resulting in a significant reduction in oil displacement efficiency. These defects of traditional PAM have become key technical bottlenecks restricting the efficient development of deep, high-salinity reservoirs.

[0003] To improve the temperature and salt resistance of PAM, several improvement strategies have been proposed in existing technologies. Firstly, copolymerization with temperature-resistant monomers aims to enhance the thermal stability and salt resistance of the molecular chain through the introduction of functional groups. However, after copolymerization with these monomers, the hydration capacity of the PAM molecular chain often weakens due to the increase in hydrophobic groups. In high-salt environments, the "ion shielding effect" can exacerbate chain shrinkage, resulting in limited improvement in viscosity retention. Secondly, chemical crosslinking is used to form a three-dimensional network structure to improve the polymer's thermal stability. However, excessive crosslinking significantly increases the rigidity of the molecular chain, making it prone to shear fracture in high-speed oil reservoir environments, leading to a rapid decline in the effective molecular weight of the polymer and unstable long-term oil displacement performance. Thirdly, composite modification with nanoparticles utilizes the high specific surface area of ​​nanomaterials to enhance the polymer's shear resistance. However, the interfacial compatibility between nanoparticles and PAM molecular chains is generally poor, leading to agglomeration. This not only prevents uniform dispersion in the polymer matrix but also accelerates polymer aging and degradation due to interfacial defects, ultimately reducing overall performance. None of the above methods fundamentally solve the problems of weak interfacial bonding between PAM molecular chains and modified components and insufficient multi-field synergistic effect, making it difficult to meet the stringent requirements of long-term stability of oil displacement agents in deep, high-temperature, and high-salinity oil reservoirs.

[0004] Against this backdrop, there is an urgent need to develop a novel modified material and its supporting preparation process, achieving efficient synergy between PAM molecular chains and modified components through multi-scale structural design, while simultaneously ensuring temperature resistance, salt resistance, and shear resistance. The gradient composite modified material and its four-step complex preparation process proposed in this invention are innovative solutions addressing these technical challenges. This material, through a ternary gradient structure design of "layered double hydroxide / polydopamine / sulfonated polyether ether ketone," achieves synergistic effects of ion shielding, interfacial adhesion, and enhanced temperature resistance. Combined with stepwise dispersion activation, gradient polymerization, and enhanced crosslinking processes, it effectively solves the problems of weak interfacial bonding and uneven dispersion in traditional modification methods. Ultimately, a novel polyacrylamide with high temperature resistance, strong salt resistance, and excellent long-term stability is prepared, providing key technical support for tertiary oil recovery in deep, high-temperature, and high-salt reservoirs. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing polyacrylamide for high-temperature and salt-resistant oilfield flooding. This method solves the technical problems of existing partially hydrolyzed polyacrylamide being prone to thermal degradation and viscosity drop due to charge neutralization in high-temperature and high-salt reservoirs, and existing modification methods having weak interfacial bonding, uneven dispersion, and poor long-term stability.

[0006] The present invention achieves the above objectives through the following technical solutions:

[0007] A method for preparing high-temperature resistant and salt-resistant polyacrylamide includes the following steps:

[0008] S1, add the layered double hydroxide / polydopamine / sulfonated polyether ether ketone ternary gradient composite modified material to deionized water, add sodium dodecyl sulfate, disperse in an ultrasonic instrument to make the layered double hydroxide / polydopamine / sulfonated polyether ether ketone ternary gradient composite modified material uniformly dispersed into a suspension, then add glutaraldehyde and stir at 40-42℃.

[0009] S2, the activated layered double hydroxide / polydopamine / sulfonated polyether ether ketone ternary gradient composite modified material suspension, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-vinylpyrrolidone, sodium acetate, and NaCl are added to the reactor, and water is added to bring the total solid content to 11-13%. After purging with nitrogen to remove oxygen, ammonium persulfate, sodium bisulfite, and isopropanol are added, and the reaction temperature gradient is controlled: the initial temperature is 30-32℃ for initiation, and then the temperature is raised to 50-54℃ for isothermal polymerization.

[0010] S3. After polymerization, transfer the gel block to a water bath, add crosslinking agent SPEEK-C, and continue the reaction at a constant temperature.

[0011] S4. After the reaction is complete, the gel block is washed with deionized water; then it is granulated, dried and pulverized.

[0012] According to a preferred embodiment of the present invention, the sodium dodecyl sulfate was purchased from Sinopharm Chemical Reagent Co., Ltd. (model: Sinopharm Chemical Reagent SDS high purity grade).

[0013] According to a preferred embodiment of the present invention, the glutaraldehyde was purchased from Aladdin Reagent (Shanghai) Co., Ltd. (model: Aladdin Glutaraldehyde Solution 50%).

[0014] According to a preferred embodiment of the present invention, the acrylamide was purchased from Tianjin Kemio Chemical Reagent Co., Ltd. (model: Kemio Acrylamide, analytical grade).

[0015] According to a preferred embodiment of the present invention, the 2-acrylamido-2-methylpropanesulfonic acid was purchased from Shandong Haoran Special Plastics Co., Ltd. (model: Haoran Special Plastics AMPS industrial grade).

[0016] According to a preferred embodiment of the present invention, the N-vinylpyrrolidone was purchased from Shanghai Yuanye Biotechnology Co., Ltd. (model: Yuanye Biotechnology N-vinylpyrrolidone analytical grade).

[0017] According to a preferred embodiment of the present invention, the sodium acetate was purchased from Sinopharm Chemical Reagent Co., Ltd. (model: Sinopharm Sodium Acetate Anhydrous Grade).

[0018] According to a preferred embodiment of the present invention, the NaCl was purchased from Tianjin Zhiyuan Chemical Reagent Co., Ltd. (model: Zhiyuan Chemical Pure Sodium Chloride).

[0019] According to a preferred embodiment of the present invention, the reactor was purchased from Weihai Automation Reactor Co., Ltd. (model: WZ series stainless steel reactor).

[0020] According to a preferred embodiment of the present invention, the nitrogen gas was purchased from Hangzhou Jingong Special Gases Co., Ltd. (model: Jingong high-purity nitrogen 99.999%).

[0021] According to a preferred embodiment of the present invention, the ammonium persulfate was purchased from Shanghai Shishihewei Chemical Co., Ltd. (model: Shishihewei ammonium persulfate analytical grade).

[0022] According to a preferred embodiment of the present invention, the sodium bisulfite was purchased from Beijing Chemical Plant (model: Beijing Chemical Plant Sodium Bisulfite, Analytical Grade).

[0023] According to a preferred embodiment of the present invention, the isopropanol was purchased from Jiangsu Qiangsheng Functional Chemical Co., Ltd. (model: Qiangsheng Isopropanol, analytical grade).

[0024] In this invention, the preparation mechanism of high-temperature and salt-resistant polyacrylamide is based on the gradient copolymerization and network reinforcement of gradient composite modified materials and monomers such as acrylamide (AM). First, the SPEEK-C crosslinking agent is activated through the ring-opening reaction of its surface amino and epoxy groups. Its double bonds form hydrogen and covalent bonds with the amino groups of PDA and the hydroxyl groups of LDH, ensuring uniform dispersion of the modified material and anchoring it in the aqueous system. Subsequently, monomers such as AM, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), and N-vinylpyrrolidone (NVP) gradually form the main chain through free radical polymerization under the action of an ammonium persulfate-sodium bisulfite redox initiation system (low-temperature initiation at 30-32℃). The low-temperature initiation stage avoids local overheating caused by rapid decomposition of the initiator, reducing molecular chain breakage; the medium-temperature isothermal stage (50-54℃) promotes the full reaction of monomers, forming a high-molecular-weight main chain. During polymerization, the double bonds of SPEEK-C copolymerize with polar groups in the monomers (such as the amide groups of AM and the sulfonic acid groups of AMPS), introducing the temperature-resistant and salt-resistant functional groups of the modified material into the polymer backbone. The amino groups of PDA and the lamellar structure of LDH bind to the backbone through interfacial forces, forming an interpenetrating network of "backbone-modified material". In the later stages of polymerization, the epoxy groups of SPEEK-C further crosslink with the hydroxyl groups of the backbone, forming a multi-layer network structure that enhances the shear resistance of the molecular chain. Finally, after washing with deionized water to remove unreacted monomers, granulation, drying, and pulverization, a high-temperature and salt-resistant polyacrylamide with high temperature resistance, strong salt resistance, and excellent long-term stability is obtained.

[0025] According to a preferred embodiment of the present invention, in step S1, the dispersion time in the ultrasonic instrument is 30-40 min; the stirring time at 40-42℃ is 2-4 h.

[0026] According to a preferred embodiment of the present invention, in step S2, the nitrogen deoxygenation time is 30-40 min; the reaction initiation time at 30-32℃ is 1-2 h; and the isothermal polymerization time at 50-54℃ is 6-8 h.

[0027] According to a preferred embodiment of the present invention, in step S3, the heat preservation reaction is continued for 2-4 hours.

[0028] According to a preferred embodiment of the present invention, in step S4, the number of times the deionized water is washed is 3-4 times; the drying temperature is 80-84℃.

[0029] According to a preferred embodiment of the present invention, the preparation steps of the aerogel-hydrogel gradient core-shell structure composite modified material include:

[0030] A1. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were dissolved in deionized water to prepare mixed solution A. NaOH and sodium carbonate were dissolved in deionized water to prepare mixed solution B. Mixed solution B was added dropwise to mixed solution A under a constant temperature water bath at 60-62℃. The pH was adjusted to 10.3-10.7, and stirring was continued. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and subjected to hydrothermal reaction at 140-144℃. After naturally cooling to room temperature, the mixture was centrifuged. The precipitate was washed with deionized water and dried under vacuum at 60-62℃ to obtain the Mg-Al LDH precursor.

[0031] A2. Disperse the Mg-AlLDH precursor in Tris buffer, add dopamine hydrochloride, stir magnetically in the dark, and after the reaction is complete, centrifuge. Wash the precipitate with deionized water until the filtrate is colorless, and dry under vacuum at 60-64℃ to obtain PDA-LDH. Dissolve polyetheretherketone in N-methylpyrrolidone, add a sulfonating agent, and stir and sulfonate at 80-82℃ to obtain SPEEK. Dissolve SPEEK in acetone, add epichlorohydrin, and react at 60-62℃ to generate an intermediate containing epoxy groups. Then, add the intermediate dropwise to an ethanol solution containing NaHSO3 and react at room temperature. Finally, add NaOH to adjust the pH to 10-10.2, precipitate the solid, filter, wash with acetone, and dry under vacuum to obtain SPEEK-C.

[0032] A3. PDA-LDH, SPEEK-C, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, and N-vinylpyrrolidone were added to deionized water to prepare an aqueous solution. Sodium acetate was added to adjust the pH to 7.0. After purging with nitrogen to remove oxygen, ammonium persulfate, sodium bisulfite, and isopropanol were added. Polymerization was carried out in a constant temperature water bath at 60-64℃. After the reaction was completed, the gel was crushed, precipitated with acetone, centrifuged, and vacuum dried at 60-62℃.

[0033] According to a preferred embodiment of the present invention, the magnesium nitrate hexahydrate was purchased from Sinopharm Chemical Reagent Co., Ltd. (model: Sinopharm magnesium nitrate hexahydrate analytical grade).

[0034] According to a preferred embodiment of the present invention, the aluminum nitrate nonahydrate was purchased from Sinopharm Chemical Reagent Co., Ltd. (model: Sinopharm aluminum nitrate nonahydrate analytical grade).

[0035] According to a preferred embodiment of the present invention, the NaOH was purchased from Sinopharm Chemical Reagent Co., Ltd. (model: Sinopharm Sodium Hydroxide Industrial Grade).

[0036] According to a preferred embodiment of the present invention, the sodium carbonate was purchased from Sinopharm Chemical Reagent Co., Ltd. (model: Sinopharm Sodium Carbonate Analytical Grade).

[0037] According to a preferred embodiment of the present invention, the polytetrafluoroethylene-lined reactor was purchased from Weihai Automation Reactor Co., Ltd. (model: WZPF series polytetrafluoroethylene-lined reactor).

[0038] According to a preferred embodiment of the present invention, the Tris buffer solution was purchased from Sangon Biotech (Shanghai) Co., Ltd.

[0039] According to a preferred embodiment of the present invention, the dopamine hydrochloride was purchased from Aladdin Reagent (Shanghai) Co., Ltd. (model: Aladdin Dopamine Hydrochloride Analytical Grade).

[0040] According to a preferred embodiment of the present invention, the polyetheretherketone (PEEK) was purchased from Zhejiang Xinhecheng Special Materials Co., Ltd. (model: Xinhecheng PEEK 450GL30).

[0041] According to a preferred embodiment of the present invention, the N-methylpyrrolidone was purchased from Puyang Huicheng Electronic Materials Co., Ltd. (model: Huicheng N-methylpyrrolidone electronic grade).

[0042] According to a preferred embodiment of the present invention, the sulfonating reagent was purchased from Sinopharm Chemical Reagent Co., Ltd. (model: Sinopharm concentrated sulfuric acid analytical grade; Sinopharm fuming sulfuric acid analytical grade).

[0043] According to a preferred embodiment of the present invention, the acetone was purchased from Sinopharm Chemical Reagent Co., Ltd. (model: Sinopharm Acetone Analytical Grade).

[0044] According to a preferred embodiment of the present invention, the epichlorohydrin was purchased from Sinopharm Chemical Reagent Co., Ltd. (model: Sinopharm epichlorohydrin analytical grade).

[0045] In this invention, the preparation mechanism of the gradient composite modified material begins with the controllable synthesis of layered double hydroxide (LDH) precursors. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate dissociate in an aqueous medium to release Mg. 2+ With Al 3+ Ions, reacting with OH- provided by sodium hydroxide and sodium carbonate. - CO3 2-The ions undergo a metathesis reaction, generating a mixed precipitate of Mg(OH)₂ and Al(OH)₃. Under constant temperature water bath conditions of 60-62℃ and weakly alkaline conditions of pH = 10.3-10.7, the mixed precipitate undergoes hydrothermal reaction (140-144℃) for crystal recombination, forming a layered Mg-Al LDH precursor. The layers are stably stacked through hydrogen bonds and electrostatic interactions, providing a high specific surface area carrier for subsequent functional layer modification. Subsequently, the LDH precursor is dispersed in Tris buffer, and dopamine hydrochloride undergoes oxidative self-polymerization in a weakly alkaline environment (pH = 8.5) to generate a polydopamine (PDA) layer containing amino (-NH₂) and phenolic hydroxyl (-OH) groups. PDA binds to the aromatic structure of the LDH layers through π-π stacking interactions, and simultaneously adsorbs onto the LDH surface through hydrogen bonds and electrostatic interactions, forming a continuous adhesion layer that significantly enhances the interfacial bonding between the subsequent functional layers and LDH. Based on this, polyetheretherketone (PEEK) is sulfonated with concentrated sulfuric acid and fuming sulfuric acid (80-82℃) to introduce sulfonic acid groups (-SO3H), generating sulfonated polyetheretherketone (SPEEK). SPEEK further undergoes a nucleophilic substitution reaction with epichlorohydrin to generate an intermediate containing epoxy groups (-CH(O)CH2-), which is then hydrolyzed with NaHSO3 and neutralized with NaOH to finally form a multifunctional crosslinking agent SPEEK-C containing double bonds (-CH=CH2), sulfonic acid groups (-SO3H), and hydroxyl groups (-OH). Thus, the LDH sheet (ion shielding), PDA adhesion layer (interfacial bonding), and SPEEK-C functional layer (temperature resistance enhancement) are sequentially loaded through stepwise reactions to form a "LDH-PDA-SPEEK-C" ternary gradient composite modified material. Its gradient structure is stabilized synergistically through interfacial forces and covalent bonds, providing multi-dimensional performance support for the polymer backbone.

[0046] According to a preferred embodiment of the present invention, in step A1, the hydrothermal reaction time at 140-144℃ is 8-10h; and the vacuum drying time at 60-62℃ is 12-14h.

[0047] According to a preferred embodiment of the present invention, in step A2, the magnetic stirring time is 24-30 h; the stirring sulfonation time at 80-82°C is 6-8 h; and the reaction time at 60-62°C is 3-5 h.

[0048] According to a preferred embodiment of the present invention, in step A3, the constant temperature water bath polymerization time at 60-64°C is 8-10 hours; the vacuum drying time at 60-62°C is 24-30 hours.

[0049] The present invention also provides an application of the high-temperature resistant and salt-resistant polyacrylamide prepared by the above preparation method in oilfield flooding.

[0050] The beneficial effects of this invention are as follows:

[0051] This invention significantly improves the high temperature resistance, salt resistance, and long-term stability of polyacrylamide through the design of novel gradient composite modified materials and a complex multi-step preparation process, demonstrating breakthrough advantages in deep, high-temperature, and high-salinity oil displacement applications.

[0052] The structural innovation of gradient composite modified materials fundamentally solves the problems of weak interfacial bonding and uneven functional dispersion in traditional modification methods. This material adopts a ternary gradient structure of "layered double hydroxide-polydopamine-sulfonated polyether ether ketone". The layered double hydroxide, through its lamellar morphology and high specific surface area, can effectively shield high-valence metal ions in the reservoir, preventing them from binding with the carboxyl groups of the polyacrylamide molecular chains and causing charge neutralization. The middle layer of polydopamine, through the oxidative self-polymerization reaction of dopamine hydrochloride, forms an adhesion layer containing amino and phenolic hydroxyl groups on the surface of the layered double hydroxide, significantly enhancing its interfacial bonding with subsequent monomers and solving the defect of easy aggregation between traditional nanomaterials and polymer matrices. The outermost sulfonated polyether ether ketone contains abundant sulfonic acid groups and temperature-resistant groups. It can increase the hydration capacity of the molecular chain through the dissociation of sulfonic acid groups to improve salt resistance, and improve the thermal stability of the molecular chain through the rigid aromatic ring structure of polyether ether ketone, thereby inhibiting the thermal degradation reaction of amide groups under high-temperature environments. This multifunctional synergistic design of the gradient structure enables the modified material and the polyacrylamide molecular chain to form a full-chain synergistic effect from ion shielding to interfacial adhesion and then to temperature resistance enhancement, laying a structural foundation for the subsequent improvement of polymer performance.

[0053] The optimization of complex preparation processes further enhanced the synergistic effect of material properties. In the dispersion and activation step, the modified material was uniformly dispersed into a nanoscale suspension through the surfactant effect of sodium dodecyl sulfate and ultrasonic dispersion technology, avoiding agglomeration. The addition of glutaraldehyde activated the polydopamine and sulfonated polyether ether ketone groups on the surface of the modified material through crosslinking reaction, enhancing its copolymerization activity with monomers such as acrylamide and 2-acrylamido-2-methylpropanesulfonic acid, enabling the modified material to be uniformly embedded in the polymer backbone in the form of chemical bonds, rather than simple physical mixing. During gradient polymerization, the initial low-temperature initiation stage ensured the slow decomposition of the initiator and the uniform generation of free radicals, avoiding molecular chain breakage caused by local overheating. The subsequent medium-temperature isothermal polymerization stage promoted the full reaction of monomers to form a high molecular weight backbone. The addition of the crosslinking agent SPEEK-C in the later stage reacted with the amino and sulfonic acid groups of polydopamine and the hydroxyl groups of the polymer backbone to form a multi-linked network, further enhancing the polymer's shear resistance and long-term stability. This phased, gradient process control effectively balances the polymerization rate, molecular weight distribution, and network structure uniformity, enabling the final product to maintain high viscosity while possessing superior anti-degradation properties. Detailed Implementation

[0054] The following detailed embodiments are only used to further illustrate this application and should not be construed as limiting the scope of protection of this application. Those skilled in the art can make some non-essential improvements and adjustments to this application based on the above application content.

[0055] Example 1

[0056] Preparation of layered double hydroxide / polydopamine / sulfonated polyether ether ketone ternary gradient composite modified material (G-MM): 2.91 g of magnesium nitrate hexahydrate and 1.11 g of aluminum nitrate nonahydrate were dissolved in 50 mL of deionized water to prepare mixed solution A; 6.4 g of sodium hydroxide and 4.24 g of sodium carbonate were dissolved in 50 mL of deionized water to prepare mixed solution B. Mixed solution B was added dropwise to mixed solution A under a constant temperature water bath at 60℃. The pH was adjusted to 10.5, and stirring was continued for 2 h. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and hydrothermally reacted at 140℃ for 8 h. After natural cooling to room temperature, the mixture was centrifuged (8000 rpm, 10 min). The precipitate was washed three times with deionized water and vacuum dried at 60℃ for 12 h to obtain the Mg-Al LDH precursor. 1.2 g of Mg-Al LDH precursor was dispersed in 1 L Tris buffer (pH = 8.5), 0.1 g of dopamine hydrochloride was added, and the mixture was magnetically stirred in the dark for 24 h. After centrifugation and washing until the filtrate was colorless, it was dried under vacuum at 60 °C for 12 h to obtain 1.0 g of PDA-LDH. 1.0 g of polyetheretherketone was dissolved in 100 mL of N-methylpyrrolidone, and a mixed sulfonating agent of 30 g concentrated sulfuric acid and 10 g fuming sulfuric acid was added. The mixture was stirred and sulfonated at 80 °C for 6 h to obtain 0.9 g of SPEEK. 0.9 g of SPEEK was dissolved in 50 mL of acetone, and 2.1 g of epichlorohydrin was added. The mixture was reacted at 60 °C for 3 h to generate an intermediate containing epoxy groups. The intermediate was then added dropwise to an ethanol solution containing 9.9 g of NaHSO3 and reacted at room temperature for 2 h. NaOH was added to adjust the pH to 10, and the precipitated solid was filtered, washed with acetone, and dried under vacuum at 60 °C for 12 h to obtain SPEEK-C. 0.8g of PDA-LDH, 0.8g of SPEEK-C, 96g of acrylamide, 12g of 2-acrylamido-2-methylpropanesulfonic acid, and 3.6g of N-vinylpyrrolidone were added to 1L of deionized water. 1.2g of sodium acetate was added to adjust the pH to 7.0. After purging with nitrogen for 30min, 3.6g of ammonium persulfate, 1.8g of sodium bisulfite, and 1.2g of isopropanol were added. The reaction was initiated at 30℃ for 1h, then heated to 50℃ and polymerized for 6h. After the reaction, the gel block was crushed, precipitated with acetone, centrifuged, and vacuum dried at 60℃ for 24h to obtain 105g of G-MM. Preparation of high-temperature resistant and salt-resistant polyacrylamide: 6g of G-MM was added to 120g of deionized water, along with 0.12g of sodium dodecyl sulfate. The mixture was ultrasonically dispersed for 30min, stirred at 40℃ for 2h, and then 0.06g of glutaraldehyde was added and stirring continued for 2h. The activated G-MM suspension (containing 6g G-MM), 96g acrylamide, 12g 2-acrylamido-2-methylpropanesulfonic acid, 3.6g N-vinylpyrrolidone, 1.2g sodium acetate, and 60g sodium chloride were added to the reactor, and water was added to bring the total solids content to 12%. After purging with nitrogen for 30 minutes, 3.6g ammonium persulfate, 1.8g sodium bisulfite, and 1.2g isopropanol were added. The reaction was initiated at 30°C for 1 hour, and then the temperature was raised to 50°C and maintained for 6 hours for polymerization.After polymerization, the gel block was transferred to a water bath, 1g of SPEEK-C was added, and the reaction was carried out at 70℃ for 2 hours. After the reaction was completed, the gel block was washed three times with deionized water, dried at 80℃ until the moisture content was <3%, and then pulverized to obtain high-temperature resistant and salt-resistant polyacrylamide.

[0057] Example 2

[0058] The specific implementation method is the same as in Example 1, except that the preparation of the layered double hydroxide / polydopamine / sulfonated polyether ether ketone ternary gradient composite modified material (G-MM) is as follows: 3.88 g of magnesium nitrate hexahydrate and 1.48 g of aluminum nitrate nonahydrate are dissolved in 50 mL of deionized water to prepare mixed solution A; 8.0 g of sodium hydroxide and 5.3 g of sodium carbonate are dissolved in 50 mL of deionized water to prepare mixed solution B. Mixed solution B is added dropwise to mixed solution A under a constant temperature water bath at 61℃, the pH is adjusted to 10.6, and stirring is continued for 2.5 h. Then, the mixture is transferred to a polytetrafluoroethylene-lined reactor and hydrothermally reacted at 142℃ for 9 h. After natural cooling to room temperature, the mixture is centrifuged (8000 rpm, 10 min). The precipitate is washed three times with deionized water and vacuum dried at 61℃ for 13 h to obtain 1.5 g of Mg-Al LDH precursor. 1.5 g of Mg-AlLDH precursor was dispersed in 1 L Tris buffer (pH = 8.5), 0.15 g of dopamine hydrochloride was added, and the mixture was magnetically stirred in the dark for 27 h. After centrifugation and washing until the filtrate was colorless, it was dried under vacuum at 61 °C for 13 h to obtain 1.2 g of PDA-LDH. 1.2 g of polyetheretherketone was dissolved in 120 mL of N-methylpyrrolidone, and a mixed sulfonating agent of 36 g of concentrated sulfuric acid and 12 g of fuming sulfuric acid was added. The mixture was stirred and sulfonated at 81 °C for 7 h to obtain 1.1 g of SPEEK. 1.1 g of SPEEK was dissolved in 60 mL of acetone, and 2.5 g of epichlorohydrin was added. The mixture was reacted at 61 °C for 4 h to generate an intermediate containing epoxy groups. Then, it was added dropwise to an ethanol solution containing 12.4 g of NaHSO3 and reacted at room temperature for 3 h. NaOH was added to adjust the pH to 10.1, the precipitated solid was filtered, washed with acetone, and dried under vacuum at 61 °C for 13 h to obtain 1.0 g of SPEEK-C. 1.0 g of PDA-LDH, 1.0 g of SPEEK-C, 120 g of acrylamide, 15 g of 2-acrylamido-2-methylpropanesulfonic acid, and 4.5 g of N-vinylpyrrolidone were added to 1.2 L of deionized water. 1.5 g of sodium acetate was added to adjust the pH to 7.0. After purging with nitrogen for 35 min, 4.5 g of ammonium persulfate, 2.25 g of sodium bisulfite, and 1.5 g of isopropanol were added. The reaction was initiated at 31 °C for 1.5 h, then heated to 52 °C and polymerized for 7 h. After the reaction, the gel block was crushed, precipitated with acetone, centrifuged, and vacuum dried at 61 °C for 25 h to obtain G-MM. Preparation of high-temperature resistant and salt-resistant polyacrylamide: 7.5 g of G-MM was added to 150 g of deionized water, along with 0.15 g of sodium dodecyl sulfate. The mixture was ultrasonically dispersed for 35 min, stirred at 41 °C for 3 h, and then 0.075 g of glutaraldehyde was added and stirring continued for another 3 h. Add the activated G-MM suspension (containing 7.5g G-MM), 120g acrylamide, 15g 2-acrylamido-2-methylpropanesulfonic acid, 4.5g N-vinylpyrrolidone, 1.5g sodium acetate, and 75g sodium chloride to the reaction vessel, and add water to bring the total solids content to 12%.After purging with nitrogen for 35 minutes, 4.5 g of ammonium persulfate, 2.25 g of sodium bisulfite, and 1.5 g of isopropanol were added. The reaction was initiated at 31°C for 1.5 hours, followed by a constant temperature polymerization at 52°C for 7 hours. After polymerization, the gel block was transferred to a water bath, and 1.2 g of SPEEK-C was added. The reaction was maintained at 70°C for 3 hours. After the reaction was complete, the gel block was washed four times with deionized water, dried at 82°C until the moisture content was <3%, and then pulverized to obtain high-temperature resistant and salt-resistant polyacrylamide.

[0059] Example 3

[0060] The specific implementation method is the same as in Example 1, except that the preparation of the layered double hydroxide / polydopamine / sulfonated polyether ether ketone ternary gradient composite modified material (G-MM) is as follows: 4.85 g of magnesium nitrate hexahydrate and 1.85 g of aluminum nitrate nonahydrate are dissolved in 50 mL of deionized water to prepare mixed solution A; 9.6 g of sodium hydroxide and 6.4 g of sodium carbonate are dissolved in 50 mL of deionized water to prepare mixed solution B. Mixed solution B is added dropwise to mixed solution A under a constant temperature water bath at 62℃, the pH is adjusted to 10.7, and stirring is continued for 3 h. The mixture is then transferred to a polytetrafluoroethylene-lined reactor and hydrothermally reacted at 144℃ for 10 h. After natural cooling to room temperature, the mixture is centrifuged (8000 rpm, 10 min). The precipitate is washed three times with deionized water and vacuum dried at 62℃ for 14 h to obtain 1.8 g of Mg-Al LDH precursor. 1.8 g of Mg-Al LDH precursor was dispersed in 1 L Tris buffer (pH = 8.5), 0.2 g of dopamine hydrochloride was added, and the mixture was magnetically stirred in the dark for 30 h. After centrifugation and washing until the filtrate was colorless, it was dried under vacuum at 62 °C for 14 h to obtain 1.5 g of PDA-LDH. 1.5 g of polyetheretherketone was dissolved in 150 mL of N-methylpyrrolidone, and a mixed sulfonating agent of 45 g concentrated sulfuric acid and 15 g fuming sulfuric acid was added. The mixture was stirred and sulfonated at 82 °C for 8 h to obtain 1.35 g of SPEEK. 1.35 g of SPEEK was dissolved in 75 mL of acetone, and 3.15 g of epichlorohydrin was added. The mixture was reacted at 62 °C for 5 h to generate an intermediate containing epoxy groups. Then, it was added dropwise to an ethanol solution containing 15.5 g of NaHSO3 and reacted at room temperature for 4 h. NaOH was added to adjust the pH to 10.2, the precipitated solid was filtered, washed with acetone, and dried under vacuum at 62 °C for 14 h to obtain 1.2 g of SPEEK-C. 1.2g of PDA-LDH, 1.2g of SPEEK-C, 144g of acrylamide, 18g of 2-acrylamido-2-methylpropanesulfonic acid, and 5.4g of N-vinylpyrrolidone were added to 1.5L of deionized water. 1.8g of sodium acetate was added to adjust the pH to 7.0. After purging with nitrogen for 40min, 5.4g of ammonium persulfate, 2.7g of sodium bisulfite, and 1.8g of isopropanol were added. The reaction was initiated at 32℃ for 2h, followed by polymerization at 54℃ for 8h. After the reaction, the gel was crushed, precipitated with acetone, centrifuged, and vacuum dried at 62℃ for 26h to obtain G-MM. Preparation of high-temperature resistant and salt-resistant polyacrylamide: 9g of G-MM was added to 180g of deionized water, along with 0.18g of sodium dodecyl sulfate. The mixture was ultrasonically dispersed for 40min, stirred at 42℃ for 4h, and then 0.09g of glutaraldehyde was added, with stirring continuing for another 4h. Add the activated G-MM suspension (containing 9g G-MM), 144g acrylamide, 18g 2-acrylamido-2-methylpropanesulfonic acid, 5.4g N-vinylpyrrolidone, 1.8g sodium acetate, and 90g sodium chloride to the reaction vessel, and add water to bring the total solids content to 12%.After purging with nitrogen for 40 minutes, 5.4 g of ammonium persulfate, 2.7 g of sodium bisulfite, and 1.8 g of isopropanol were added. The reaction was initiated at 32°C for 2 hours, followed by a constant temperature polymerization at 54°C for 8 hours. After polymerization, the gel block was transferred to a water bath, and 1.5 g of SPEEK-C was added. The reaction was maintained at 70°C for 4 hours. After the reaction was completed, the gel block was washed four times with deionized water, dried at 84°C until the moisture content was <3%, and then pulverized to obtain high-temperature resistant and salt-resistant polyacrylamide.

[0061] Comparative Example 1

[0062] The specific implementation method is the same as in Example 1, except that 96g of acrylamide, 12g of 2-acrylamido-2-methylpropanesulfonic acid, 3.6g of N-vinylpyrrolidone, 1.2g of sodium acetate, and 60g of sodium chloride are added to 1L of deionized water, and water is added to bring the total solid content to 12%. After purging with nitrogen for 30 minutes, 3.6g of ammonium persulfate, 1.8g of sodium bisulfite, and 1.2g of isopropanol are added. The reaction is initiated at 30°C for 1 hour, and then the temperature is raised to 50°C for 6 hours of constant-temperature polymerization. After polymerization, the gel block is transferred to a water bath, 1g of SPEEK-C (a conventional sulfonated polyether ether ketone crosslinking agent) is added, and the reaction is maintained at 70°C for 2 hours. After the reaction is complete, the gel block is washed three times with deionized water, dried at 80°C until the moisture content is <3%, and then pulverized to obtain polyacrylamide.

[0063] Comparative Example 2

[0064] The specific implementation method is the same as in Example 1, except that the preparation of layered double hydroxide (LDH) is as follows: 2.91 g of magnesium nitrate hexahydrate and 1.11 g of aluminum nitrate nonahydrate are dissolved in 50 mL of deionized water to prepare mixed solution A; 6.4 g of sodium hydroxide and 4.24 g of sodium carbonate are dissolved in 50 mL of deionized water to prepare mixed solution B. Mixed solution B is added dropwise to mixed solution A under a constant temperature water bath at 60°C, the pH is adjusted to 10.5, and stirring is continued for 2 hours. The mixture is then transferred to a polytetrafluoroethylene-lined reactor and hydrothermally reacted at 140°C for 8 hours. After natural cooling to room temperature, the mixture is centrifuged (8000 rpm, 10 min). The precipitate is washed three times with deionized water and dried under vacuum at 60°C for 12 hours to obtain Mg-Al LDH. Preparation of high-temperature and salt-resistant polyacrylamide: 6g of LDH was added to 120g of deionized water, followed by 0.12g of sodium dodecyl sulfate. The mixture was ultrasonically dispersed for 30min, stirred at 40℃ for 2h, and then 0.06g of glutaraldehyde was added and stirring continued for another 2h. The activated LDH suspension (containing 6g of LDH), 96g of acrylamide, 12g of 2-acrylamido-2-methylpropanesulfonic acid, 3.6g of N-vinylpyrrolidone, 1.2g of sodium acetate, and 60g of sodium chloride were added to a reactor, and water was added to bring the total solid content to 12%. After purging with nitrogen for 30min, 3.6g of ammonium persulfate, 1.8g of sodium bisulfite, and 1.2g of isopropanol were added. The reaction was initiated at 30℃ for 1h, followed by a constant temperature polymerization at 50℃ for 6h. After polymerization, the gel block was transferred to a water bath, 1g of SPEEK-C was added, and the reaction was maintained at 70℃ for 2h. After the reaction was completed, the gel block was washed three times with deionized water, dried at 80°C until the moisture content was <3%, and then pulverized to obtain polyacrylamide.

[0065] Comparative Example 3

[0066] The specific implementation method is the same as in Example 1, except that the preparation of polydopamine (PDA) is as follows: 1.2 g of Mg-Al LDH precursor is dispersed in 1 L of Tris buffer (pH = 8.5), 0.1 g of dopamine hydrochloride is added, and the mixture is magnetically stirred in the dark for 24 h. After centrifugation and washing until the filtrate is colorless, it is vacuum dried at 60 °C for 12 h to obtain PDA-LDH. The preparation of high-temperature resistant and salt-resistant polyacrylamide is as follows: 6 g of PDA-LDH is added to 120 g of deionized water, 0.12 g of sodium dodecyl sulfate is added, and the mixture is ultrasonically dispersed for 30 min. After stirring at 40 °C for 2 h, 0.06 g of glutaraldehyde is added and stirring is continued for 2 h. The activated PDA-LDH suspension (containing 6 g of PDA-LDH), 96 g of acrylamide, 12 g of 2-acrylamido-2-methylpropanesulfonic acid, 3.6 g of N-vinylpyrrolidone, 1.2 g of sodium acetate, and 60 g of sodium chloride are added to the reaction vessel, and water is added to bring the total solids content to 12%. After purging with nitrogen for 30 minutes, 3.6 g of ammonium persulfate, 1.8 g of sodium bisulfite, and 1.2 g of isopropanol were added. The reaction was initiated at 30°C for 1 hour, followed by a constant temperature polymerization at 50°C for 6 hours. After polymerization, the gel block was transferred to a water bath, 1 g of SPEEK-C was added, and the reaction was maintained at 70°C for 2 hours. After the reaction was complete, the gel block was washed three times with deionized water, dried at 80°C until the moisture content was <3%, and then pulverized to obtain polyacrylamide.

[0067] Performance testing

[0068] The high-temperature resistant and salt-resistant polyacrylamide for oilfield flooding prepared by the above-mentioned preparation processes of Examples 1-3 and Comparative Examples 1-3 was subjected to performance testing according to the following methods.

[0069] First, the intrinsic viscosity of a 0.1% (mass fraction) polyacrylamide solution was determined using an Ubbelohde viscometer (capillary inner diameter 0.5 mm, nominal volume 10 mL) in a 25℃ constant temperature water bath. Specifically, 10 mL of the defoamed solution was slowly injected along the viscometer tube wall using a pipette, and the time t1 for the solution to flow through the scale line a to b was measured. This was repeated three times, and the average value was taken. Simultaneously, the time t0 for deionized water to flow through the solution was measured (at least three times, with a relative error ≤ 0.2%). The intrinsic viscosity was calculated using the formula [η] = (t - t0) × K / ρ (where K is the viscometer constant, and ρ is the solution density, approximately 1 g / cm³). 3 Next, the 0.1% solution was placed in a 90℃ constant temperature oven for 30 days for aging, and the intrinsic viscosity [η] after aging was measured using the method described above. a Calculate the viscosity retention rate Rt = [η] after aging at 90℃ for 30 days. a / [η]0×100%; then prepare a mineralization degree of 15×10 4 mg / L (containing NaCl 12×10) 4 mg / L, CaCl2 2×10 4 mg / L, MgCl2 1×104 Dissolve 0.1% polyacrylamide in a solution of (mg / L), measure the intrinsic viscosity [η]s at 25℃, measure [η]as after aging at 90℃ for 30 days, and calculate 15×10. 4 mg / L mineralization viscosity retention rate Rs=[η]as / [η]s×100%; Shear resistance test was performed using a rotational viscometer (rotor model LV-4, speed range 0-1000r / min) to measure the viscosity of a 0.1% solution at a shear rate of 10s. -1 100s -1 500s -1 1000s -1 Calculate the apparent viscosity η under the given conditions for 1000 s. -1 Shear viscosity retention rate Rγ=η 1000 / η0×100% (η0 is 0s) -1 (Viscosity at time); the oil displacement efficiency test was conducted using a long core displacement device (core length 30cm, diameter 2.5cm, permeability 100×10⁻⁶). -3 μm 2 ), core saturated simulated formation water (mineralization 15×10⁻⁶) 4 After injecting 0.3 PV (pore volume) of 0.1% polyacrylamide solution (injection rate 0.1 mL / min), 0.2 PV of simulated formation water displacement is injected after the injection is completed. The produced fluid is collected and weighed. The oil displacement efficiency is calculated according to the formula E = (original oil content - remaining oil content) / original oil content × 100% (the original oil content is determined by the mass difference after the core is saturated with crude oil).

[0070] Test results:

[0071] Table 1: Test results of each embodiment and comparative example

[0072]

[0073]

[0074] As can be seen from Table 1, the high-temperature and salt-resistant polyacrylamide prepared in Examples 1-3 shows significant improvement in core properties such as temperature resistance, salt resistance, shear resistance, and long-term stability compared to Comparative Examples 1-3. It effectively solves the technical problems of existing partially hydrolyzed polyacrylamide (HPAM) in high-temperature and high-salt reservoirs, such as easy thermal degradation, charge neutralization leading to a sharp drop in viscosity, as well as the weak interfacial bonding, uneven dispersion, and poor long-term stability of traditional modification methods.

[0075] In terms of thermal degradation performance, existing HPAMs are prone to thermal decomposition of amide groups at 90℃, resulting in rapid decrease in intrinsic viscosity due to molecular chain breakage. The viscosity retention rate of Comparative Examples 1-3 after 30 days of aging at 90℃ is only 38%-45%. However, Examples 1-3, through gradient composite modification materials (containing polyether ether ketone heat-resistant groups and polydopamine interfacial adhesion layer), enhance the thermal stability of the molecular chain, and their viscosity retention rate after 30 days of aging at 90℃ is increased to 82%-88%, indicating that the degree of thermal degradation of the molecular chain is significantly reduced, thus solving the problem of easy thermal degradation of traditional HPAMs.

[0076] From the perspective of salt resistance, high-valence ions (such as Ca) in high-salinity reservoirs... 2+ Mg 2+ This neutralizes the carboxylate charge on the HPAM molecular chain, disrupts the hydration layer, and causes a sharp drop in viscosity. Comparative Examples 1-3 show this at 15 × 10⁻⁶. 4 The viscosity retention rate at a salinity of mg / L is only 25%-30%; Examples 1-3 effectively suppress the neutralization effect of high-valence ions through the ion shielding effect of layered double hydroxide (LDH) and the synergistic effect of the sulfonic acid anti-salt groups of sulfonated polyether ether ketone (SPEEK-C), with a viscosity of 15×10⁻⁶ mg / L. 4 The viscosity retention rate at a mineralization concentration of mg / L increased to 75%-81%, significantly enhancing salt resistance.

[0077] From the perspective of interfacial bonding and dispersibility, traditional modification methods (such as nanoparticle blending) are prone to uneven dispersion due to poor interfacial compatibility. Comparative Example 2 (containing only LDH) and Comparative Example 3 (containing only PDA) have limited performance improvement due to weak interfacial bonding between the modified material and PAM (viscosity retention rate is less than 46%). Examples 1-3 adopt the "LDH-PDA-SPEEK-C" ternary gradient structure design, which utilizes the amino and phenolic hydroxyl groups of polydopamine (PDA) to form a strong interfacial bond with PAM. At the same time, the lamellar structure of layered double hydroxide (LDH) disperses stress, avoids the agglomeration of modified materials, and achieves uniform dispersion of functional components in the PAM matrix, significantly improving the interfacial synergistic effect.

[0078] In terms of long-term stability, existing modification methods (such as chemical crosslinking) often lead to increased molecular chain rigidity and severe shear degradation due to excessive crosslinking, as seen in Comparative Examples 1-3, which show a 1000s degradation rate. -1 The shear viscosity retention rate is only 32%-38%; Examples 1-3, through a gradient crosslinking network (multiple crosslinking of SPEEK-C with PDA and LDH) and the rigid structure of polyetheretherketone, enhance shear resistance while maintaining molecular chain flexibility, achieving a 1000s... -1 The shear viscosity retention rate was increased to 68%-72%, and the core flooding efficiency (62%-66%) was significantly higher than that of the control group (43%-47%), indicating that the performance degradation rate was lower and the stability was better during long-term use.

[0079] In summary, through the design of novel gradient composite modified materials and a multi-step complex process, Implementation Series 1-3 systematically solved the problems of thermal degradation, charge neutralization, weak interfacial bonding and poor long-term stability of existing HPAM, and showed superior oil displacement performance in high-temperature and high-salinity reservoirs.

[0080] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing high-temperature resistant and salt-resistant polyacrylamide, characterized in that, Includes the following steps: S1. Add the layered double hydroxide / polydopamine / sulfonated polyether ether ketone ternary gradient composite modified material to deionized water, add sodium dodecyl sulfate, disperse in an ultrasonic instrument to make the layered double hydroxide / polydopamine / sulfonated polyether ether ketone ternary gradient composite modified material uniformly dispersed into a suspension, then add glutaraldehyde and stir at 40-42℃. S2, the activated layered double hydroxide / polydopamine / sulfonated polyether ether ketone ternary gradient composite modified material suspension, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-vinylpyrrolidone, sodium acetate, and NaCl are added to the reactor, and water is added to bring the total solid content to 11-13%. After purging with nitrogen to remove oxygen, ammonium persulfate, sodium bisulfite, and isopropanol are added, and the reaction temperature gradient is controlled: the initial temperature is 30-32℃ for initiation, and then the temperature is raised to 50-54℃ for isothermal polymerization. S3. After polymerization, transfer the gel block to a water bath, add crosslinking agent SPEEK-C, and continue the reaction at a constant temperature. S4. After the reaction is complete, the gel block is washed with deionized water; then it is granulated, dried and pulverized.

2. The method for preparing high-temperature resistant and salt-resistant polyacrylamide according to claim 1, characterized in that, In step S1, the dispersion time in the ultrasonic instrument is 30-40 min; the stirring time at 40-42℃ is 2-4 h.

3. The method for preparing high-temperature resistant and salt-resistant polyacrylamide according to claim 1, characterized in that, In step S2, the nitrogen purging time for deoxygenation is 30-40 min; the reaction initiation time at 30-32℃ is 1-2 h; and the isothermal polymerization time at 50-54℃ is 6-8 h.

4. The method for preparing high-temperature resistant and salt-resistant polyacrylamide according to claim 1, characterized in that, In step S3, the reaction is continued at a constant temperature for 2-4 hours.

5. The method for preparing high-temperature resistant and salt-resistant polyacrylamide according to claim 1, characterized in that, In step S4, the washing with deionized water is performed 3-4 times; the drying temperature is 80-84℃.

6. The method for preparing high-temperature resistant and salt-resistant polyacrylamide according to any one of claims 1-5, characterized in that, The preparation steps of the aerogel-hydrogel gradient core-shell structure composite modified material include: A1. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were dissolved in deionized water to prepare mixed solution A. NaOH and sodium carbonate were dissolved in deionized water to prepare mixed solution B. Mixed solution B was added dropwise to mixed solution A under a constant temperature water bath at 60-62℃. The pH was adjusted to 10.3-10.7, and stirring was continued. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and subjected to hydrothermal reaction at 140-144℃. After naturally cooling to room temperature, the mixture was centrifuged. The precipitate was washed with deionized water and dried under vacuum at 60-62℃ to obtain the Mg-Al LDH precursor. A2. Mg-Al LDH precursor was dispersed in Tris buffer, dopamine hydrochloride was added, and the mixture was magnetically stirred in the dark. After the reaction was complete, the mixture was centrifuged, and the precipitate was washed with deionized water until the filtrate was colorless. The precipitate was then dried under vacuum at 60-64℃ to obtain PDA-LDH. Polyether ether ketone was dissolved in N-methylpyrrolidone, a sulfonating agent was added, and the mixture was stirred and sulfonated at 80-82℃ to obtain SPEEK. SPEEK was dissolved in acetone, epichlorohydrin was added, and the mixture was reacted at 60-62℃ to generate an intermediate containing epoxy groups. The intermediate was then added dropwise to an ethanol solution containing NaHSO3 and reacted at room temperature. Finally, NaOH was added to adjust the pH to 10-10.2, and a solid precipitated. The solid was filtered, washed with acetone, and dried under vacuum to obtain SPEEK-C. A3. PDA-LDH, SPEEK-C, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, and N-vinylpyrrolidone were added to deionized water to prepare an aqueous solution. Sodium acetate was added to adjust the pH to 7.

0. After purging with nitrogen to remove oxygen, ammonium persulfate, sodium bisulfite, and isopropanol were added. Polymerization was carried out in a constant temperature water bath at 60-64℃. After the reaction was completed, the gel was crushed, precipitated with acetone, centrifuged, and vacuum dried at 60-62℃.

7. The method for preparing high-temperature resistant and salt-resistant polyacrylamide according to claim 6, characterized in that, In step A1, the hydrothermal reaction time at 140-144℃ is 8-10 hours; the vacuum drying time at 60-62℃ is 12-14 hours.

8. The method for preparing high-temperature resistant and salt-resistant polyacrylamide according to claim 6, characterized in that, In step A2, the magnetic stirring time is 24-30 hours; the sulfonation time at 80-82℃ is 6-8 hours; and the reaction time at 60-62℃ is 3-5 hours.

9. The method for preparing high-temperature resistant and salt-resistant polyacrylamide according to claim 6, characterized in that, In step A3, the polymerization time in a constant temperature water bath at 60-64℃ is 8-10 hours; the vacuum drying time at 60-62℃ is 24-30 hours.

10. An application of a high-temperature resistant and salt-resistant polyacrylamide prepared by the preparation method according to any one of claims 1-9, characterized in that, The application of high-temperature resistant and salt-resistant polyacrylamide in oilfield flooding.